2012
DOI: 10.1080/14427591.2011.639135
|View full text |Cite
|
Sign up to set email alerts
|

Being Occupied with What Matters in Advanced Age

Abstract: This article illuminates one key finding of an interpretive phenomenological study that brought an occupational lens to exploring how elders experience ageing in their everyday lives. Fifteen community-dwelling, New Zealand elders aged 71 to 97, 4 Maori and 11 nonMaori, were purposively recruited. Data were gathered through individual interviews focused on stories of everyday moments and photographs of the participant's hands only while engaged in doing a chosen occupation. Discrete stories were drawn from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…Consideration of personal values – what matters to people – is therefore essential if participation in advanced age is to be promoted. A similar finding was reported by Wright-St Clair (2012) when exploring the experience of being aged in everyday life. The notion of ‘doing what matters’ was of primary importance in advanced age, with engagement in an enduring, compelling pursuit evoking a deep sense of identity and contentment.…”
Section: Discussionsupporting
confidence: 88%
“…Consideration of personal values – what matters to people – is therefore essential if participation in advanced age is to be promoted. A similar finding was reported by Wright-St Clair (2012) when exploring the experience of being aged in everyday life. The notion of ‘doing what matters’ was of primary importance in advanced age, with engagement in an enduring, compelling pursuit evoking a deep sense of identity and contentment.…”
Section: Discussionsupporting
confidence: 88%
“…This could be achieved by addressing a wider range of needs as opposed to prioritising physical and mental functions’ limitations and lack of independent living skills . The type of activities provided for elderly persons with physical disabilities should align with their preferences and promote participation in ways that are meaningful to them. This can be achieved through elderly persons’ experiences of competency or a sense of self, acting in accordance with personal values, or dealing with the complexities of growing older, to name but a few ways to achieve this . Furthermore, the persons in this study were observed to oscillate between the three strategies of approaching problematic situations. This might also be considered as avoiding any of the strategies’ drawbacks and utilising their benefits.…”
Section: Discussionmentioning
confidence: 82%
“…Researchers identified everyday activities as offering elderly persons platforms to recreate or experience a sense of self that allows them to embrace life and to continue, test and adapt their identity , as found when Mr Muranaka sought an effective strategy to mitigate the implications of his disability. Research showing that engaging in meaningful activities by elderly persons contribute to them ageing well was also evident in Ms Kunitani referring to her drawing as ‘rehabilitation for my soul’. A theme about doing the right thing from an earlier study and other research emphasise moral dimensions of engaging with everyday activities .…”
Section: Discussionmentioning
confidence: 94%
“…Greater exploration of older adults' participation in "personally compelling" occupations that provide meaning and occupational identity across the lifespan has also been called for (Wright-St Clair, 2012). Therefore, the aim of this study was to gain a deeper understanding of the participation in social activism by older adults in Ireland, defined as those aged 65 and over.…”
Section: Social Activism Among Older Adults: Benefits Risks and Motimentioning
confidence: 99%